Respuesta :
Answer:
f+g = -2x+1
Step-by-step explanation:
Hey there! I will make your learning easier and clearer! If you have any doubts or questions, feel free to comment below!
We are given both functions:
[tex] \displaystyle \large{f(x) = 3x - 6} \\ \displaystyle \large{g(x) = - 5x + 7}[/tex]
Since we want to find f+g which also means (f+g)(x), we just combine both functions!
[tex] \displaystyle \large{f + g = (3x - 6) + ( - 5x + 7)}[/tex]
Cancel all brackets and combine like terms!
[tex] \displaystyle \large{f + g = 3x - 6 - 5x + 7} \\ \displaystyle \large{f + g = - 2x + 1} \\ [/tex]
From above, combine 3x-5x = -2x and -6+7 = 7-6 = 1.
Still don't get it? Let's say we simply combine both functions or add both functions when we want to find f+g.
Ex.
For example, we are given f(x) = x+2 and g(x) = 2x+1. Find f+g.
We simply combine both functions and thus:-
f+g = x+2+2x+1
f+g = 3x+3 { 3(x+1) }
Answer:
f+g = 2x+1
Step-by-step explanation:
...............